Improvement of the cardiopulmonary capacity of patients with chronic obstructive pulmonary disease of Kinshasa by training of aerobic endurance and resistance - Mabele Godefroid Kusuayi; Ekisawa Constant Nkiama; Ngasa Nicias Kiana; Nzeloka Jolie Bongo; Ntumba Jean Marie Kayembe (Turkish Journal of Kinesiology, 2018)
The objective is to determine the effect of aerobic endurance training and resistance on cardiorespiratory fitness in patients with Chronic Obstructive Pulmonary Disease in Kinshasa, Democratic Republic of Congo. In a follow-up study with a duration of 36 weeks, between March and May 2018, 30 mismatched patients with a mean age of 49 ± 9.7 years followed after medical management at the Kinesiology Department's medical fitness laboratory and functional exercises of University Clinics of Kinshasa, were subject to an aerobic endurance and resistance training program of 3 days per week, for one hour 30 minutes per day, three sets of 20 minutes of work and 10 minutes of rest, of moderate intensity including: treadmill walking, ergo-cycle exercises with progressive loading and respiratory gymnastics. The paired Student T test was used to compare the continuous variables before and after the program. A significant decrease in most of the parameters studied respectively: (- 23 bpm) p <0.0001 for resting heart rate; (- 26 bpm); p <0.0001 for heart rate immediately after exercise (-10 mm Hg); p <0.0001 for systolic blood pressure; (- 8 cycles per minute); p <0.0001 for the respiratory rate; (- 20.7%); p <0.0001 for workload (intensity of effort) and (- 10 minutes); p <0.0001 for dyspnea on exertion. On the other hand, a significant increase of: (+ 2.6 liter per second); p <0.0001 for Peak Expiratory Flow; (+ 19%); p <0.0001 for the Tiffeneau index; (+ 51minutes); p <0.0001 for the duration of sensation of fatigue during exercise; (+ 6%), p <0.0001 for oxygen saturation in the open air and (+ 640 meters); p <0.0001 for the walking area. A training program for aerobic endurance and resistance significantly improves the stress tolerance of patients with Chronic Obstructive Pulmonary Disease and can be considered as an effective non-pharmacological management for the improvement of physical capacity as well as the quality of life of these patients.